Participation among marginalized young people in Brazil using action research to support subjective well-being in volunteering - Aked, Jody (2012)
People have recognized the intrinsic value of informal exchanges of time, energy, and resources for creating a social context that supports human well-being. Attempts to harness these benefits by nongovernment and government agencies have led to the organization of structured platforms to nurture voluntary acts of public service and pro-social behavior. The instrumental value of volunteering remains a debated topic warranting investigation of the relationship between volunteering, well-being, and active citizenship. A growing body of evidence in the western world suggests that positive mental states and good functioning often precede and help to cause good outcomes; that while it is possible for volunteering opportunities to feed an upward spiral of advantages for individuals involved, they can also exacerbate inequalities between individuals. Using the concept of subjective well-being and action research as method, the paper explores ways of working with the dynamic nature and unequal distribution of subjective well-being to support the participation of marginalized groups.
Keywords: Young people -- Brazil; Well-being -- Brazil; Volunteering